1999
DOI: 10.1002/(sici)1521-4176(199904)50:4<219::aid-maco219>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Betrachtungen über den Zusammenhang zwischen bakteriellem Wachstum und der mikrobiell induzierten Potentialverschiebung bei nichtrostenden Stählen

Abstract: Ausgangspunkt für die vorliegende Untersuchung waren Korrosionsschäden an Kühlwasserrohrleitungen aus nichtrostenden Stählen, die unterhalb von 50°C durch mikrobielle Beläge verursacht wurden. Diese Biofilme bewirkten eine Potentialverschiebung der Werkstoffe in den Bereich der labilen Lochfraßbeständigkeit. Die mikrobiologische und elektrochemische Untersuchung ergab, daß die bakteriellen Zelldichten in den Belägen ebenso temperaturabhängig sind wie die im Laborexperiment erreichten Endwerte des Freien Korros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…At the University of Applied Sciences in Konstanz test equipment was developed and used to examine the influence of different parameters on the microbial caused potential rise of stainless steels [13,14]. To analyse MIC, a new testing-facility has been designed consisting of sealed glass vessels with five sealed openings on top of each vessel (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…At the University of Applied Sciences in Konstanz test equipment was developed and used to examine the influence of different parameters on the microbial caused potential rise of stainless steels [13,14]. To analyse MIC, a new testing-facility has been designed consisting of sealed glass vessels with five sealed openings on top of each vessel (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…During examinations of corrosion damaged SS-components from various industrial plants slimy brownish biofilms were identified. It was found that part of these deposits consists of oxides and hydroxides of Mn in higher oxidation states and that a significant portion of the bacteria detected is able to produce MnO 2 [1,2].…”
Section: Introductionmentioning
confidence: 99%